South Asia as a Reservoir for the Global Spread of Ciprofloxacin-Resistant Shigella sonnei: A Cross-Sectional Study. - Hao Chung The; Maia A Rabaa; Duy Pham Thanh; Niall De Lappe; Martin Cormican; Mary Valcanis; Benjamin P Howden; Sonam Wangchuk; Ladaporn Bodhidatta; Carl J Mason; To Nguyen Thi Nguyen; Duong Vu Thuy; et al. (PLoS Medicine)
Background Antimicrobial resistance is a major issue in the Shigellae, particularly as a specific multidrug-resistant (MDR) lineage of Shigella sonnei (lineage III) is becoming globally dominant. Ciprofloxacin is a recommended treatment for Shigella infections. However, ciprofloxacin-resistant S. sonnei are being increasingly isolated in Asia and sporadically reported on other continents. We hypothesized that Asia is a primary hub for the recent international spread of ciprofloxacin-resistant S. sonnei. Methods and findings We performed whole-genome sequencing on a collection of 60 contemporaneous ciprofloxacin-resistant S. sonnei isolated in four countries within Asia (Vietnam, n = 11; Bhutan, n = 12; Thailand, n = 1; Cambodia, n = 1) and two outside of Asia (Australia, n = 19; Ireland, n = 16). We reconstructed the recent evolutionary history of these organisms and combined these data with their geographical location of isolation. Placing these sequences into a global phylogeny, we found that all ciprofloxacin-resistant S. sonnei formed a single clade within a Central Asian expansion of lineage III. Furthermore, our data show that resistance to ciprofloxacin within S. sonnei may be globally attributed to a single clonal emergence event, encompassing sequential gyrA-S83L, parC-S80I, and gyrA-D87G mutations. Geographical data predict that South Asia is the likely primary source of these organisms, which are being regularly exported across Asia and intercontinentally into Australia, the United States and Europe. Our analysis was limited by the number of S. sonnei sequences available from diverse geographical areas and time periods, and we cannot discount the potential existence of other unsampled reservoir populations of antimicrobial-resistant S. sonnei. Conclusions This study suggests that a single clone, which is widespread in South Asia, is likely driving the current intercontinental surge of ciprofloxacin-resistant S. sonnei and is capable of establishing endemic transmission in new locations. Despite being limited in geographical scope, our work has major implications for understanding the international transfer of antimicrobial-resistant pathogens, with S. sonnei acting as a tractable model for studying how antimicrobial-resistant Gram-negative bacteria spread globally.